Thermal bridges in buildings of consolidated contexts in high-altitude cities. Case study: Ambato, Ecuador - Pazmiño, Lucía (2023)
This research work has been centered on the study of thermal bridges in the urban area of the city of Ambato, this city is located at an altitude of 2570m with an average temperature of 15°C throughout the year, the construction systems used in the study area mostly consist of a layer of material either clay brick or concrete block and exterior and interior finishing's. The objective is to diagnose the points where thermal leaks can be found in consolidated environments and to provide possible solutions in different construction elements. The methodology used is based on a mixed study, which analyzes the urban context, the buildings present, the construction materials used, their relationship with the current climate of the area and the quantification of latent temperatures for further simulation. The results were obtained through a calculation software where the diagnosis and the improvement plan were simulated to increase the ambient temperature of the houses from 15-17°C to the range of 20-24°C within the comfort temperature range for interior spaces. This study concluded that it is possible to significantly improve the thermal performance of buildings in consolidated contexts with specific interventions.